2014
DOI: 10.1007/s12471-014-0617-x
|View full text |Cite
|
Sign up to set email alerts
|

High survival rate of 43% in out-of-hospital cardiac arrest patients in an optimised chain of survival

Abstract: AimsSurvival to hospital discharge after out-of-hospital cardiac arrest (OHCA) varies widely. This study describes short-term survival after OHCA in a region with an extensive care path and a follow-up of 1 year.MethodsConsecutive patients ≥16 years admitted to the emergency department between April 2011 and December 2012 were included. In July 2014 a follow-up took place. Socio-demographic data, characteristics of the OHCA and interventions were described and associations with survival were determined.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 11 publications
3
44
4
2
Order By: Relevance
“…While numerous studies investigated survival rates after OHCA in different European countries, this is the first study investigating different features of OHCA resuscitation in Croatia, including the survival rate (3). Although our results are far from the survival rate of 43% in Netherlands (21) or 35% in Osaka Prefecture, Japan (22), the survival rate until discharge after OHCA of 14% in Varaždin County exceeds OHCA overall survival rate in Europe (9%) (1), part of Poland (10%) (23), or Czechia (9%) (24), with the latter two having similar cultural characteristics as Croatia. Such a good survival rate is probably due to the prompt response time of 6 minutes and physician-staffed EMS team, but we also showed that the survival rate to discharge was associated with the conduction of bystander CPR.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…While numerous studies investigated survival rates after OHCA in different European countries, this is the first study investigating different features of OHCA resuscitation in Croatia, including the survival rate (3). Although our results are far from the survival rate of 43% in Netherlands (21) or 35% in Osaka Prefecture, Japan (22), the survival rate until discharge after OHCA of 14% in Varaždin County exceeds OHCA overall survival rate in Europe (9%) (1), part of Poland (10%) (23), or Czechia (9%) (24), with the latter two having similar cultural characteristics as Croatia. Such a good survival rate is probably due to the prompt response time of 6 minutes and physician-staffed EMS team, but we also showed that the survival rate to discharge was associated with the conduction of bystander CPR.…”
Section: Discussioncontrasting
confidence: 77%
“…This bystander CPR rate is slightly higher than in Germany (19%) (25) or Slovenia (22%) (26). Despite of this, we feel that our goal should be set higher, toward the bystander CPR rates of about 40%, as is the case in the United States (27) and England (28), or 76% in the Netherlands (21). …”
Section: Discussionmentioning
confidence: 99%
“…However, our data is consistent with similar series in dedicated units that included patients after admission to the ACCU, with an initial rhythm reported as VF and using mild hypothermia [29,30]. Therefore, the study population may be skewed towards patients with FNP, since patients who died in transit or survived to hospital admission but died in the emergency department or during the hypothermia protocol, before withdrawing sedation, were excluded.…”
Section: Limitationssupporting
confidence: 84%
“…Such high rates are attributable to various prehospital improvements and public training initiatives. (14)(15)(16)(17)(18) Pertinent to our study, Norway, (19)(20)(21) Sweden (14,17) and Denmark, (15) for example, have successfully mandated various schoolbased CPR and AED trainings over the years as part of their overall strategy to improve OHCA survival outcomes. (5,15,(19)(20)(21) The success in Europe and Seattle (22) inspired Singapore to adopt a multifaceted approach to improve bystander CPR rates.…”
Section: Introductionmentioning
confidence: 93%